2017
DOI: 10.1128/aac.02121-16
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin B in Combination with Rifampin and Meropenem against Polymyxin B-Resistant KPC-Producing Klebsiella pneumoniae

Abstract: Safe and effective therapies are urgently needed to treat polymyxinresistant KPC-producing Klebsiella pneumoniae infections and suppress the emergence of resistance. We investigated the pharmacodynamics of polymyxin B, rifampin, and meropenem alone and as polymyxin B-based double and triple combinations against KPC-producing K. pneumoniae isolates. The rates and extents of killing with polymyxin B (1 to 128 mg/liter), rifampin (2 to 16 mg/liter), and meropenem (10 to 120 mg/liter) were evaluated against polymy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…The increased in vitro bacterial effect of double-or triple-drug combinations of colistin or polymyxin B and various drugs, such as rifampin (6,7), meropenem (8,9), and amikacin (10,11), has been well demonstrated in many studies. Azithromycin is the most commonly prescribed antibiotic, other than for the clinical treatment of serious Gram-negative infections because of poor diffusion across the outer membrane of most Gram-negative bacteria (12).…”
mentioning
confidence: 99%
“…The increased in vitro bacterial effect of double-or triple-drug combinations of colistin or polymyxin B and various drugs, such as rifampin (6,7), meropenem (8,9), and amikacin (10,11), has been well demonstrated in many studies. Azithromycin is the most commonly prescribed antibiotic, other than for the clinical treatment of serious Gram-negative infections because of poor diffusion across the outer membrane of most Gram-negative bacteria (12).…”
mentioning
confidence: 99%
“…Triple combinations, although infrequently used in the United States, may be necessary for prolonged sustained activity to treat infections due to highly resistant K. pneumoniae isolates. Previous studies have suggested a clinical and microbiological benefit to three-drug combinations (7,26). Moreover, adding an additional drug such as a carbapenem or fosfomycin to the polymyxin B and minocycline combination may increase efficacy against KPC-producing K. pneumoniae by increasing the log kill rate of polymyxin B with minocycline to theoretically slow any regrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Time-kill studies. The bacterial killing activity of polymyxin B and minocycline as monotherapies and in combination was evaluated against the six isolates by performing time-kill experiments over 48 h using methods previously described (26). Polymyxin B concentrations of 0.5, 1, 2, 4, and 16 mg/liter and minocycline concentrations of 1, 2, 4, 8, and 16 mg/liter were evaluated as monotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro models of infection include static time-kill, dynamic onecompartment, and hollow-fiber systems; in vivo infection models typically utilize neutropenic mice. 3,4 However, current preclinical translational designs and models fail to take the host immune response, which is key to initiating bacterial clearance and clinical outcome, into account. The interaction between the invading bacterial pathogen and host innate immune system is the principal pathway for elimination of virulent extracellular grampositive and gram-negative pathogens from the lung, tipping the immune balance toward inflammation.…”
Section: Study Highlightsmentioning
confidence: 99%
“…Current translational research primarily optimizes existing antibiotics against these hard‐to‐treat pathogens using in vitro and in vivo infection pharmacokinetic (PK) and pharmacodynamic (PD) models of drugs and bacteria. In vitro models of infection include static time‐kill, dynamic one‐compartment, and hollow‐fiber systems; in vivo infection models typically utilize neutropenic mice …”
mentioning
confidence: 99%